Poleward range expansion of a tropical coral reef fish (Centropyge flavissima) to Lord Howe Island, Australia - Hobbs, Jean-Paul (Cambridge University Press, 2010)
The lemonpeel angelfish (Centropyge flavissima) was recorded for the first time at Lord Howe Island, Australia, whilst SCUBA diving at 20 m depth on 26 March 2009. This represents a southward range expansion of more than 1000 km for this coral reef fish into temperate waters. The range expansion was probably facilitated by the dispersal of larvae from the southern Great Barrier Reef via the southward flowing East Australian Current and enhanced overwinter survival due to rising sea temperatures.